Therapeutic Communication in Trauma Recovery for Students Surviving of Sexual Violence - Orwela, Citra (PALASTREN: Jurnal Studi Gender, 2022)
Sexual violence is one of the unresolved issues up to now. Several efforts have been made by the government such as providing LPA protection and safe houses in several areas in order to minimize the case of sexual violence. However, this issue has still been found in the community, in the area of City and District of Kediri. The research used a multi case study approach by conducting interviews and observing sexual violence survivors and associates from NGOs KIBAR and WCC Kilisuci. The researcher was actively participated and involved in mentoring activities. It was found that there were 3 stages of therapeutic communication; The first stage is the pre-counseling process in the form of collecting data from survivor reports, survivors' friends or survivors' families. The second stage, the counseling process is carried out by taking a persuasive approach to build the level of trust of the survivors and their families towards the assocaites volunteers. The third stage, post mentoring process for recovery communication after all case counseling processes are completed.